The Influence of Water Temperature on Seawater Evaporation in the Desalination Process - Sayuti, Adi Tegar; Mugisidi, Dan; Wirangga, Ristanto; Heriyani, Oktarina (Universitas Muhammadiyah Jakarta, 2023)
Population An increase in population in an area results in an increased demand for clean water. Although water is abundant, about 97% of the water on Earth is seawater, which cannot be consumed directly because it contains harmful substances. Desalination process is used to convert seawater into drinking water by utilizing heat and wind speed. This research explores temperatures of 30℃, 45℃, 60℃, and 70℃ with a wind speed of 2.6 m/s. Data was collected for each temperature variation for 2 hours with records every 15 minutes, aiming to evaluate the effectiveness of evaporation and condensation in the desalination process. The results showed that 70℃ resulted in the highest evaporation (800 grams), although with a condensation rate of 26.25%. Condensate measurements showed a pH of 7.2 and TDS meter readings ranged from 125 to 138 ppm.